Enhanced high-fructose syrup production by an hybrid fermentation/pervaporation system using a silicone rubber hollow fiber membrane module. - Gagné, Isabelle. (University of Ottawa (Canada), 2001)
In this study, a mutant of the yeast Saccharomyces cerevisiae was used for the selective conversion of glucose to ethanol using feed solutions of sucrose. Batch fermentation using 30% (w/v) sucrose without membrane separation of ethanol required about 27 hours for glucose to be decreased to 2% (w/v), with a fructose yield of 99%, and an ethanol yield of 78%. Batch fermentation using 30% (w/v) sucrose with membrane separation of ethanol required about 16.5 hours for glucose to be decreased to 2% (w/v), with a fructose yield of 96.5% and an ethanol yield of 79.5%, if the membrane was started after 6 hours of batch mode. The process required about 15 hours if the membrane was started after 3 hours of batch mode, with a fructose yield of 92%, and an ethanol yield of 82%. In fed-batch mode the yeast was able to process the equivalent of a 40% (w/v) sucrose feed in 24 hours, compared to well over 40 hours without ethanol removal, with yields of, 98% fructose, and 82% ethanol. (Abstract shortened by UMI.)
Keywords: Agriculture, Food Science and Technology.